Effect of empty fruit bunch biochar application on soil properties and sweet corn (Zea mays L.) growth / Norfazida Ali - Ali, Norfazida (Faculty of Plantation and Agrotechnology, 2016)
Biochar as soil amendment has potential increased the soil pH and improve plant growth. Biochar has many agricultural benefits. It increases crop yields. It helps to prevent fertilizer runoff and leaching, allowing the use of less fertilizers and diminishing agricultural pollution to the surrounding environment. The study test on the effect of different rates of EFB biochar applied on soil planted with sweet com (Zea mays L). This study was conducted at UiTM Melaka, Campus Jasin. A glasshouse experiment was conducted to study the effect of empty fruit bunch (EFB) biochar application on soil pH and plant growth. There were five treatments used which 0, 2.5, 5, 10, and 20 t/ha. Treatments were arranged in completely randomized block design with three replication. Results of the study showed that the soil pH was increased with the increased application of EFB biochar. Besides that, plant height also show the improvement after application of EFB biochar on soil.